Exploring awareness of hearing loss and ear health in Jordanian adults. - Yazan Gammoh; Rama Alasir; Laila Qanawati (PLoS ONE)
Objective To assess the awareness about hearing loss and ear health among adults in Jordan. Methods A cross-sectional study was conducted where a questionnaire was filled from the month of November to the month of December of the year 2023, to assess the level of awareness about hearing loss and ear health. The participants included were Jordanian adults (age ≥ 18 years) residing in the North, Middle and South of Jordan. Results Data from 333 participants (54.1% men) were analyzed. Participants between 18 and 28 years of age comprised 29.7% of the sample population. More than half of the participants (52.6%) held a university degree. Overall percentage of correct responses was 83%. Women, postgraduate degree holders, and participants diagnosed with hearing loss had an average of 11.96±1.47, 12.65±1.59 and 11.70±1.69 correct answers, respectively. The highest correct response received (97.6%) was for: hearing aids need to fit accurately to provide the maximum benefit. Furthermore, 97% of the sample correctly acknowledged that sudden hearing loss is an emergency and requires an immediate audiological assessment. The main misconception was that a deaf-mute cannot speak because of defects in the vocal tract, with only 39.3% of the sample providing a correct response. The other two misconceptions were: cotton buds are necessary for ear cleaning and are the safest means, and that ear drops are sufficient to treat earache, with 78.1% correct responses for each statement. Participants with higher level of education had higher odds of answering the questions correctly, with limited role observed for gender, prior diagnosis of hearing loss and a family history of hearing loss. Conclusions and relevance Majority of the adults surveyed provided a correct answer to the hearing loss and ear health survey. While most of the sample population were aware that a sudden loss of hearing is considered an emergency, only one third knew that defects in vocal cords do not play a role in deafness/muteness. The study highlights the need of public education on causes of hearing loss and measures needed to prevent the onset of hearing loss, with emphasis on methods for caring of ear health.